Strategi Pembelajaran dalam Pengembangan Fisik Motorik Anak Usia Dini Studi Kasus di RA At-Taufiq dan TK AL- Azhar 33 - Ana Marlina; Ayu Tasya Siti Fatimah; Rifa Farhanatul Kamilah; Rizka Aulia Nursya`Bani; Virgina Cahya Hardianto; Winarni Putria Chandra (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe the implementation of physical motor development in early childhood at RA At-Taufiq and Al-Azhar Islamic Kindergarten in Tasikmalaya. A qualitative approach was used with a case study method. Data was obtained through observation, interviews, and documentation, then analysed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show that through planned and meaningful play, both institutions prioritise the development of children's motor skills. At RA At-Taufiq, emphasis is placed on children's physical health and discipline through regular exercise, nutritional checks, and reducing the consumption of packaged foods. Meanwhile, TK Islam Al-Azhar incorporates Islamic values into motor activities through nasyid gymnastics, thematic games, and outdoor learning activities. Through running, jumping, and kicking balls, both institutions improve children's gross motor skills and fine motor skills. Daily observations and anecdotal notes are the correct ways to evaluate development. Observations show that regular physical motor activities carried out in context can improve children's coordination, strength, agility, and concentration. Thus, planned and consistent physical motor development has been proven to be beneficial in supporting the overall development of early childhood